Temporal Team Mental Model and Performance: From the Perspective of Team Process - Li, Dan; Zhang, Qian (Frontiers in Psychology, 2021)
This paper, based on the survey data of 506 knowledge-based innovation team leaders, employed the regression model and adopted the bootstrap method, to explore the influence of the temporal team mental model on team performance from the perspective of team process. The study results showed that the temporal team mental model has a significant positive predictive effect on team performance; behavioral integration has a mediating effect between temporal team mental model and team performance; task complexity positively moderates the relationship between behavioral integration and team performance, and moderates the mediating effects of behavioral integration.